Heartwood of Secang (CAESALPINIA SAPPAN L.) Ethanolic Extract Show Selective Cytotoxic Activities on T47D and Widr Cells But Not on Hela Cells - Erlina Rivanti; Bani Adlina Shabrina; Ika Nurzijah; Cyndwika Ayu; Adam Hermawan (Indonesian Society for Cancer Chemoprevention, 2016)
The present study investigate the selectivity of heartwood of secang ethanolic extract (SEE) on T47D breast cancer cells, WiDr colon cancer cells, and HeLa cervical cancer cells, compared to Vero normal epithelial cells. The cytotoxic effect was evaluated by using MTT assay with 24-hour treatment to get IC50values. Selectivity was evaluated by using selectivity index (SI). SEE had a potent cytotoxic activity on T47D and WiDr cancer cells (IC50 <100 µg/ml). IC50 value of HeLa cancer cells was observed on moderate cytotoxic (100 <IC50 <1000 µg/ml). SEE demonstrated more selective to T47D and WiDr than Vero cells (SI > 3), while in HeLa cells is not selective (SI < 3). This result indicating its potential of Caesalpinia sappan as a chemopreventive agent in cancer therapy.Keywords: Cancer, selectivity, Secang, T47D, WiDr, HeLa, Vero